Perlindungan undang-undang harta intelek cap dagangan di Malaysia dan Indonesia - Ahmad Shamsul Abd Aziz, (Fakulti Undang - Undang, 2005)

(untitled)
Trade mark is one of the branches in intellectual property. It is an identification sign of a product and services. Trade mark is so important that it enables consumers to choose a product on quantities and prices offered. Legal protection on it is vital especially in order to determine who is the lawful owner of it and to prevent growth in counterfeiting activities. The most apparent difference with regards to protection provided by laws in Malaysia and Indonesia is the need for registration. In our country, any infringement of unregistered mark is actionable under common law principles of passing-off